A Tactical Games Model lesson plan to teach net games skills in elementary school - Antonella Quinto; Teresa Iona; Michele Barca; Francesco Sgrò (Formazione & Insegnamento)
The study aimed to assess the efficacy of two physical education approaches, Traditional Teaching (TT) and Tactical Games Model (TGM), on some fourth-grade classes over a 13-weeks period. Using the Game Performance Assessment Instrument (GPAI), indices of tactical awareness and game play skills were measured. Data were collected at two intervals: pre and post intervention. The mixed ANOVA analysis revealed that, prior to the administration of the protocols, the skill levels between the TT and TGM classes were largely comparable. However, following the intervention, the TGM classes demonstrated superior performance in some indices of the GPAI compared to the TT classes. Within-subject analysis indicated no improvement in tactical awareness and gameplay skills for the TT classes over time. In contrast, the TGM classes exhibited significant improvement from pre to post test in some indices. These findings substantiate the efficacy of the Tactical Games Model (TGM) in significantly enhancing students’ performance, particularly in terms of tactical awareness and gameplay skills, when compared to conventional pedagogical approach, thereby highlighting the potential of TGM to foster a deeper understanding of game dynamics and improve overall physical education outcomes.